2012
DOI: 10.4088/jcp.11m07624
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Injurious Road Traffic Crash After Prescription of Antidepressants

Abstract: Patients and prescribers should be warned about the risk of crash during periods of treatment with antidepressant medication and about particularly high vulnerability periods such as those when a treatment is initiated or modified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 0 publications
1
31
0
Order By: Relevance
“…The stratified case–control analysis showed similar results in both subgroups . A recent case–crossover study showed that the risk of crash was increased in users who initiated an antidepressant treatment and a case–control analysis showed an increased risk of responsibility in the crash for all antidepressant users . Risk estimates in case–control studies are a combination of the effect of medicines in regular users, the effect of medicines in occasional users and the effect of depression symptoms.…”
Section: Introductionmentioning
confidence: 62%
“…The stratified case–control analysis showed similar results in both subgroups . A recent case–crossover study showed that the risk of crash was increased in users who initiated an antidepressant treatment and a case–control analysis showed an increased risk of responsibility in the crash for all antidepressant users . Risk estimates in case–control studies are a combination of the effect of medicines in regular users, the effect of medicines in occasional users and the effect of depression symptoms.…”
Section: Introductionmentioning
confidence: 62%
“…Depression was not assessed. Orriols et al (Orriols et al 2012) did a case-crossover analysis of 72,685 drivers in France using the national health care insurance database and the national police database and found an OR of 1.34 for crash and prescription of antidepressants as a class (95% CI, 1.22 to 1.47). SSRIs (OR = 1.30; 95% CI, 1.16 to 1.46), SNRIs (OR = 1.51; 95% CI, 1.25 to 1.84), and other antidepressants (OR = 1.30; 95% CI, 1.01 to 1.67) also had a significant association with increased risk of crash.…”
Section: Resultsmentioning
confidence: 99%
“…al (LeRoy & Morse 2008), Ravera et.al (Ravera et al 2011), Sagberg et.al (Sagberg 2006), Orriols et. al (Orriols et al 2012)) were included in the quantitative meta-analysis on antidepressant use and crash risk (Table 2). Two studies (Bramness et.…”
Section: Resultsmentioning
confidence: 99%
“…The association between drivers’ use of benzodiazepines and the risk of road crash is now consistently documented [914]. Other medicines have also been studied: antidepressants [10,1317], opioids used in pain treatment and in substitution treatment for opioid dependence [11,13,18,19], and cardiovascular drugs [20,21]. A positive association was found in these studies, except for 1 study [20] that found no association between calcium channel blockers and the risk of crash, and 2 studies [11,19] in which there was an increased risk with opioid use, but the increase was not statistically significant.…”
Section: Introductionmentioning
confidence: 99%